Increasing Red Onion Production on a Household Scale Using Coconut Water and NPK as a Growth Stimulant - Ardian, Ardian; Syafrinal, Syafrinal; Nurbaiti, Nurbaiti; Zuhry, Elza; Kurnia Sari, Lisa; Lubis, Nursiani (Politeknik Negeri Lampung., 2024)
Red onion (Allium ascalonicum L.) is a horticultural plant needed by household consumers as a complement to cooking spices and traditional medicines. Shallot production does not meet market demand in Riau, so it is necessary to bring in shallots from other regions. Efforts to increase shallot production continue to be made to meet market demand in Riau. One of the efforts that can be made to increase the production of shallot plants is through the use of natural growth hormones (ZPT). This research aims to determine the respective effects and interactions of giving concentrations of coconut water and NPK fertilizer on the growth and yield of shallot production. This research is a factorial experiment prepared using a completely randomized design (CRD) consisting of 2 factors, namely the concentration of coconut water and the dose of NPK fertilizer. Factor I: Coconut water concentration which consists of 4 levels, namely: A0 = without coconut water, A1 = 50% coconut water (500 ml coconut water + 500 ml water), A2 = 75% coconut water (750 ml coconut water + 250 ml water) and A3 = 100% coconut water (1000 ml coconut water). Factor II: NPK fertilizer dose consisting of 3 levels, namely: N1 = NPK 125 kg.ha-1, N2 = NPK 250 kg.ha-1, and N3 = NPK 375 kg.ha-1. . Data from the analysis of variance were further tested using Duncan's multiple range test at the 5% level. The research results showed that the combination of coconut water with a concentration of 100% and NPK fertilizer with a dose of 250 kg.ha-1 increase plant height, increase tuber diameter, increase fresh tuber weight per m2 and weight of storable tubers per m2.